Vpliv zastirke na zadrževanje vlage v prsti - Vovk Korže, Ana (Revija za geografijo, 2013)
In the northeastern Slovenia in recent decades suffer from frequent droughts, which inhibit the growth of cultivated plants. With the purpose of naturally increase the humidity of the soil, we used mulches. Mulches protects the soil from increased moisture loss, reduces the need for watering, prevents erosion, leaching and soil compaction, and the soil with mulches is not necessary to loosen. Where the soil is covered with mulches, it is also less weeds, which had a positive effect on plant growth and reduce evaporation from the soil. With the fieldwork we were monitored moisture content of the soil in the meadown and fields and in the profiles, which were covered with mulches and without mulches profiles. The findings show that could be used to mulches significantly increased moisture retention in soils, where it plays an important role in the way the use of your soil.
Keywords: kmetijska zemljišča; mulčenje; pedologija; prst (pedologija); vlaga; zastiranje tal